2019
DOI: 10.1080/15592294.2019.1600388
|View full text |Cite
|
Sign up to set email alerts
|

MiR-155-5p modulates HSV-1 replication via the epigenetic regulation of SRSF2 gene expression

Abstract: A previous study reported that miR-155-5p knockout mice were more resistant to herpes simplex virus type I (HSV-1) infection. However, the exact underlying molecular mechanism remains to be elucidated. Here, we demonstrated that HSV-1 infection upregulates miR-155-5p expression. By binding to the promoter of serine/arginine-rich splicing factor 2 (SRSF2), which is an important transcriptional activator of HSV-1 genes that was previously reported by our group, and altering the histone modification located near … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 48 publications
2
15
0
Order By: Relevance
“…miR‐155 is abundantly expressed in dendritic cells, macrophages, active B cells, and T cells . In the present study, exogenous expression of miR‐155 in the brains of ICR suckling mice showed a protective effect against life‐threatening DENV infection (Figure 3).…”
Section: Discussionsupporting
confidence: 55%
“…miR‐155 is abundantly expressed in dendritic cells, macrophages, active B cells, and T cells . In the present study, exogenous expression of miR‐155 in the brains of ICR suckling mice showed a protective effect against life‐threatening DENV infection (Figure 3).…”
Section: Discussionsupporting
confidence: 55%
“…Hsa-miR-155-5p has been reported to modulate viral replication and viral gene expression in HSV-1 infections. 44 The functional analysis showed that these ceRNA network-related mRNAs were involved in regulating the immune system, T cell activation, the TNF signaling pathway, and the IL-17 signaling pathway. We speculated that lncRNA NEAT1 may also participate in regulating the immune response, cytokine storms or antiviral processes against SARS-CoV-2 by binding with key miRNAs, such as hsa-miR-100-5p and hsa-miR-155-5p.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30] Recently, it has been found that miR-155 can change the transcription initiation site of the serine/argininerich splicing factor 2 (SRSF2) promoter and regulate the protein kinase A (PKA) signaling pathway. 31 These findings suggest that miR-155 is directly or indirectly involved in epigenetic regulation.…”
Section: Introductionmentioning
confidence: 94%